The psychological well-being, emotional distress and resilience in adolescents living with thalassemia in maldives - Mansoor, Shanooha (2013)
This study was conducted with the aim of assessing the psychological well-being emotional distress and level of resilience in adolescents living with Thalassemia in Maldives. Eighty one adolescents living with Thalassemia in Maldives, who presented to the Thalassemia centre between March 2013 and May 2013 was included in the study. The subject’s psychological well-being, emotional distress and resilience were studied. The pedsQL 4.0 generic scale was used to asses psychological wellbeing, while the Depression, Anxiety, Stress Scale (DASS-21) was used to assess the level of their emotional distress. The Resilience Scale was utilized to assess the subject’s resilience level. SPSS version 19.0 was used for statistical analysis. The level of psychological well-being was found to be 79.50 (95% Cl 75.84, 83.15), while the level of emotional distress, in terms of depression was at 4.18 (95% Cl 3.19, 5.18), stress at 4.59 (95% Cl 3.60, 5.58) and anxiety was at 4.47 (95% Cl 3.51, 5.42). Resilience level fell into the moderate category with a score of 131.6 (95% Cl 125.57, 137.58). PWB was found to have a significant but reverse correlation with emotional distress, which included stress (r = -0.632, p<0.05), depression (r = -0.628, p<0.05) and anxiety (r = -0.476,p <0.05). Resilience was found to have a significant but poor positive correlation with psychological wellbeing, while a negative correlation existed with depression. A ferritin level of more than 2500p/l had a significant effect on PWB (t (74) = 2.36, p <0.05) and anxiety (t (70.04) = 2.43, p<0.05) .The study showed that younger subjects were more resilient (r = 0.22, p<0.05). The females have lower PWB compared to the male subjects (t = 2.36, p<0.05). A significant linear negative relationship between gender, depressive symptoms and stress symptoms with psychological well-being was obtained. Where those who are male have 6.52 unit lower psychological wellbeing (adjusted b=-6.52, 95% Cl -11.97,-1.07), p=0.020), while those depressed have 1.54 unit lower psychological well-being (adjusted b=-1.54, 95% Cl -2.48 0.60), p=0.002) and those stressed have 1.12 unit lower psychological well-being (adjusted b=-1.12, 95% Cl -2.50, 0.19), p=0.018). The study showed that emotional distress had a negative impact on psychological well-being of adolescents living with Thalassemia in Maldives. It also found that those with lower resilience were more likely to be depressed. However resilience did not play a role in anxiety and stress. The psychological well-being was found to be higher in those with high levels of resilience. It was also found that gender, depressive symptoms and stress symptoms were predictors PWB of thalassemia adolescents.